2022
DOI: 10.1159/000524903
|View full text |Cite
|
Sign up to set email alerts
|

Severe Bullous Pemphigoid Onset after Jugular Catheter Placement in a Patient on Hemodialysis

Abstract: Pruritus is highly prevalent in the dialysis population. Its etiology however remains often unclear with uremic pruritus primarily suspected unless compelling evidence of another cause. Although bullous pemphigoid (BP) is considered idiopathic, there are growing data in the literature on BP provoked by different factors, such as medications or surgical procedures. These secondary dermatoses are described as rather mild conditions and more frequent in the elderly Caucasian. We herein describe a newly dialyzed A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Doxycycline, a second-generation tetracyclines, does not require dose adjustment when used in patients with renal impairments ( 86 ). Two of the three patients recovered by using doxycycline in conjunction with topical corticosteroids ( 18 , 19 ), while the other was recalcitrant to doxycycline and other drugs, including systemic corticosteroids, dapsone, and niacinamide ( 44 ). A recent multicenter randomized controlled trial showed that doxycycline displayed a comparable efficacy in BP treatment to oral corticosteroids with minimized adverse events ( 87 ).…”
Section: Resultsmentioning
confidence: 99%
“…Doxycycline, a second-generation tetracyclines, does not require dose adjustment when used in patients with renal impairments ( 86 ). Two of the three patients recovered by using doxycycline in conjunction with topical corticosteroids ( 18 , 19 ), while the other was recalcitrant to doxycycline and other drugs, including systemic corticosteroids, dapsone, and niacinamide ( 44 ). A recent multicenter randomized controlled trial showed that doxycycline displayed a comparable efficacy in BP treatment to oral corticosteroids with minimized adverse events ( 87 ).…”
Section: Resultsmentioning
confidence: 99%